A combined approach for modifying pea protein isolate to greatly improve its solubility and emulsifying stability. (30th June 2022) - Zhi, Zijian; Yan, Lei; Li, Hao; Dewettinck, Koen; Van der Meeren, Paul; Liu, Rui; Van Bockstaele, Filip
Highlights: A combined approach was developed to modify the pea protein isolate (PPI). The PPI solubility was tripled after PUH modification. The modification mechanism of PPI was clearly elucidated. The physical and storage stability of emulsions with modified PPIs markedly improved. Abstract: Pea protein-based delivery systems have drawn much attention in the food and pharmaceutical fields in recent years. However, its broad application faces great limitations because of the low solubility. Here, we present a novel and effective approach to overcome this difficulty and enhance the techno-functional characteristics, especially emulsifying stability, of the pea protein isolate (PPI). By combining pH-shifting with ultrasound and heating (PUH), we concluded that the solubility of PPI greatly increased from 29.5 % to 90.4 %, whereas its surface hydrophobicity increased from 1098 to 3706. This was accompanied by the changes of PPI structure, as shown by circular dichroism and scanning electron microscopy. In addition, the modified PPI was applied to stabilize sunflower oil-in-water emulsions. The droplet size of the emulsion with PUHP was reduced and its emulsion stability was significantly elevated. Taken together, we propose a novel combined approach to prepare modified PPI with high solubility and emulsion stability. We expect our method will have a wider application in modifying plant proteins and improving their industrial processing.